Analisis Interaksi Postur dengan Peralatan Kerja Menggunakan Metode Rapid Office Strain Assessment (Rosa) Pada Pekerja Kantor X - Luthfi, Muhammad (UI Scholars Hub, 2022)
Workers in any industry are at risk for Work-related Musculoskeletal Disorders (WMSDs) including office administration workers. This study aims to analyze the interaction of posture with work equipment using the rapid office strain assessment (ROSA) method to assess the ergonomic risk factor. This study found typing is an area requiring ergonomic intervention with chair is more influential (52%) than monitors and other office equipment (48%). Meanwhile other equipment that affects worker posture is mouse and keyboard (62%) compared to telephone and monitor (38%). WMSDs in office administration workers are strongly affected by the chair, mouse and keyboard.